Direct growth of FeS2 on paper: A flexible, multifunctional platform for ultra-low cost, low power memristor and wearable non-contact breath sensor for activity detection. (15th March 2020) - Veeralingam, Sushmitha; Khandelwal, Shivam; Sha, Rinky; Badhulika, Sushmee
Abstract: This is the first demonstration of direct growth of iron pyrite (FeS2 ) via a single step hydrothermal route on low cost, biodegradable, flexible cellulose paper substrate which is further explored as a versatile multifunctional platform for memristor (with top and bottom electrodes) and wearable breath sensor (with planar contacts) which exhibits excellent switching and response respectively. XRD, EDAX studies confirmed the formation of crystalline pyrite FeS2. Memristor device exhibits excellent bipolar resistive switching mechanism at very low set, reset voltages i.e. +0.25 V, −0.5 V with a very low power consumption in the range of few micro to nano watts, decent switching ratio of 4 × 10 2, good data retention up to 2 × 10 4 s and excellent switching endurance up to 500 cycles. Furthermore, FeS2 grown on paper displayed excellent response towards exhaled breath exhibiting distinguished response towards oral and nasal breath. The sensor was employed in monitoring the exhaled breath pattern during dynamic movements like walking, running and jumping. The mechanism of sensing can be attributed to the conductivity and hydrophilic nature of sensor aiding in adsorption and desorption of the water molecules from the exhaled breath on to the FeS2 microspheres. The strategy outlined here, presents a low cost approach using iron and its pyrites which are abundant, non-toxic and also cost effective based flexible devices for multifunctional electronic applications. Graphical abstract: Image 1